2013
DOI: 10.1002/jgra.50467
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence rate of extreme magnetic storms

Abstract: [1] We investigate the occurrence rate of magnetic storms at the Earth. During the first part of our study, the standard and integral distribution functions of magnetic storm value (minimal Dst index) for the period 1963-2012 are analyzed and results show that the standard and integral distribution functions have power law tails with indexes = -4.4 and -3.4, respectively. During the second part, statistical analysis of occurrence rate of magnetic storms induced by different types of interplanetary drivers is m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
0
30
0
5
Order By: Relevance
“…Kataoka (2013) estimated that the probability of a Carrington-type geomagnetic storm occurring within the next decade is approximately 4% to 6%. Yermolaev et al (2013) performed a statistical analysis of the OMNI data for the period 1976 to 2000 and concluded that a Carrington-type event could occur once every 500 years (see also Alves et al 2011). From the flare onset to the geomagnetic storm onset, Carrington (1859) gave a time of approximately 17.5 h from the flare to the storm, which indicates a CME speed of approximately 2,360 km/s (Gopalswamy et al 2005c).…”
Section: Extreme Space Weathermentioning
confidence: 99%
“…Kataoka (2013) estimated that the probability of a Carrington-type geomagnetic storm occurring within the next decade is approximately 4% to 6%. Yermolaev et al (2013) performed a statistical analysis of the OMNI data for the period 1976 to 2000 and concluded that a Carrington-type event could occur once every 500 years (see also Alves et al 2011). From the flare onset to the geomagnetic storm onset, Carrington (1859) gave a time of approximately 17.5 h from the flare to the storm, which indicates a CME speed of approximately 2,360 km/s (Gopalswamy et al 2005c).…”
Section: Extreme Space Weathermentioning
confidence: 99%
“…The very low statistical significance of severe storms is a key issue for model calibration, that is fed by data mainly from moderate to intense disturbances, due to the lack of severe storms in the sample (Srivastava 2005;Kataoka 2013;Yermolaev et al 2013). Carrington (1859) connected ''two patches of intensely bright and white light'' in a large solar spot with ''a moderate but very marked magnetic disturbance of short duration'' in Kew magnetic records followed by the commencement of a great magnetic storm.…”
Section: Introductionmentioning
confidence: 99%
“…The SYM-H value (the symmetric disturbance index for the H-component, 1 min time cadence) for this storm was −710 nT (Lakhina and Tsurutani 2016). The occurrence rate of a storm comparable to the March 1989 storm has been estimated to be once every 60 years (Tsubouchi and Omura 2007;Riley 2012;Kataoka 2013), although it has been argued that such storms cannot be predicted with reasonable accuracy (Willis et al 1997;Tsurutani et al 2003;Love 2012;Yermolaev et al 2013;Love et al 2015;Lakhina and Tsurutani 2016). The solar wind parameters were not very extreme at the time of the 1989 storm.…”
Section: Rc-type Slow Gicsmentioning
confidence: 93%